Estudo dos ostracodes das formações cantaure (Mioceno) e Paranaguá (Plioceno) da Venezuela no contexto da região caribenha - CASTELO, Wellen Fernada Louzada (2019)
The uplift of the Panama Isthmus between North and South America was one of the most important events occurred during the Neogene, once allowed the union of two continents after 50 million years of isolation resulting in the separation of Atlantic and Pacific Oceans, and therefore in great changes, whether physical or chemical. This study aimed to conduct the survey of ostracofauna from Cantaure Formation (Early Miocene) and Paraguaná (Lower Pliocene) in Paraguaná Peninsula, Venezuela, and to take stock of existing genres that after the close connection between the Atlantic and Pacific oceans, contributing to scientific knowledge about Caribbean region. This is the first study specifically with ostracodes these formations. The material study consisted of a total of five samples, three from Cantaure and two from Paraguaná. Were found a total of 32 genera of ostracodes in Cantaure Formation and 13 in Paraguaná Formation. The difference in diversity between Cantaure and Paraguaná formations is probably linked with the final uplift of Panama Isthmus, which occurred in the Pliocene and it is associated with a drop in salinity and decrease the amount of nutrients available. The reduction of the fauna occurred in the interval between Miocene and Pliocene agree what was said by other authors for the Caribbean region. A fauna with 2.6% endemism in the lower Miocene has decreased to 1.2% in the Pliocene. Among the marine fauna associated were found carophytas and the ostracod genre Ilyocypris in Paraguaná Fm, which are indicators of freshwater to mixohalinos environments, suggesting that this peninsula was some influenced by a river.